Long‐term outcome of enzyme‐replacement therapy in advanced Fabry disease: evidence for disease progression towards serious complications. (6th May 2013) - Weidemann, F.; Niemann, M.; Störk, S.; Breunig, F.; Beer, M.; Sommer, C.; Herrmann, S.; Ertl, G.; Wanner, C.
Abstract: Objective: The long‐term effects of enzyme‐replacement therapy (ERT) in Fabry disease are unknown. Thus, the aim of this study was to determine whether ERT in patients with advanced Fabry disease affects progression towards 'hard' clinical end‐points in comparison with the natural course of the disease. Methods: A total of 40 patients with genetically proven Fabry disease (mean age 40 ± 9 years; n  = 9 women) were treated prospectively with ERT for 6 years. In addition, 40 subjects from the Fabry Registry, matched for age, sex, chronic kidney disease stage and previous transient ischaemic attack (TIA), served as a comparison group. The main outcome was a composite of stroke, end‐stage renal disease (ESRD) and death. Secondary outcomes included changes in myocardial left ventricular (LV) wall thickness and replacement fibrosis, change in glomerular filtration rate (GFR), new TIA and change in neuropathic pain. Results: During a median follow‐up of 6.0 years (bottom and top quartiles: 5.1, 7.2), 15 events occurred in 13 patients ( n  = 7 deaths, n  = 4 cases of ESRD and n  = 4 strokes). Sudden death occurred ( n  = 6) only in patients with documented ventricular tachycardia and myocardial replacement fibrosis. The annual progression of myocardial LV fibrosis in the entire cohort was 0.6 ± 0.7%. As a result, posterior end‐diastolic wall thinning was observed (baseline, 13.2 ± 2.0 mm; follow‐up, 11.4 ± 2.1 mm; P  < 0.01). GFR decreased by 2.3 ± 4.6 mL min −1 per year. Three patients experienced a TIA. The major clinical symptom was neuropathic pain ( n  = 37), and this symptom improved in 25 patients. The event rate was not different between the ERT group and the untreated (natural history) group of the Fabry Registry. Conclusion: Despite ERT, clinically meaningful events including sudden cardiac death continue to develop in patients with advanced Fabry disease.